The Existence of the Nahdlatul Ulama Party in the Guided Democracy Era - Rina Andriani Hidayat (Lakpesdam PCNU Kota Salatiga, 2022)
This paper was motivated by the success of Nahdlatul Ulama to become the most prominent Islamic political party during the Guided Democracy period. In addition, at the time, Nahdlatul Ulama Party (PNU) played an essential role in the national political scene as one of the main components of the